A Uniform Asymptotical Upper Bound for the Variance of a Random Polytope in a Simple Polytope - A. Magazinov (Моделирование и анализ информационных систем, 2015)
The present paper contains a sketch of the proof of an upper bound for the variance of the number of hyperfaces of a random polytope when the mother body is a simple polytope. Thus we verify a weaker version of the result in [1] stated without a proof. The article is published in the author’s wording.